Развитие аналитических тенденций в русском языке в области представления неприязненных эмоциональных отношений - Кожинова, Алла А.; Камрани Мотлаг, Эльхам (Papers in Linguistics, 2020)
The article investigates the role of derivational analytic constructions such as to propagate contempt, to display enmity, to inflate hatred.